Rios de reciprocidade : saberes tradicionais no contexto da sustentabilidade socioambiental na comunidade Mem de Sá - Itaporanda D´Ajuda-SE - Aragão, Míria Cássia Oliveira (2011)
This dissertation aims to analyze the logic of survival of fishermen from Mem de Sa community Itaporanga D´Ajuda/SE, in the perspective of social and environmental sustainability. The study setting is the community Mem de Sá situated in a river island in the estuary of Vaza-Barris river, (11°29´26´´S and 06´46´´W), located in Itaporanga D´Ajuda, only 26 km away from the seat of the municipality and 53 km from Aracaju, capital of Sergipe state. The specific objectives of the study are: to build sustainability indicators that enable the verification of the possibilities and limitations of fishing activity, to characterize the importance of the environment on the composition of the territory and on the carried fishing practices, to identify the knowledge, rituals and myths surrounded the community and, to perform the monitoring of the fishing community. The main question that the chapters try to answer is: how the logic of survival of fishermen is configured and what is the interference of environmental, social, cultural, political and economic factors on the activities developed in the fishing community in Mem de Sá Itaporanga D´Ajuda/SE. The first chapter describes the research scenario. The second chapter presents the theoretical framework. The third chapter focuses on social and environmental dynamics based on sustainability indicators of social and environmental dimension. In the fourth chapter are included the analysis of political and economic indicator. The fifth chapter covers the cultural/spiritual sustainability indicator. And finally, the sixth chapter expresses the intention to understand the logic of life of fishermen, caught in its essence and understood by its own light. Therefore, the proposed research is inseparable from traditional knowledge originated from relation webs of community Mem de Sá, whether with members of its internal or external community or with environment of their experience, however, social and environmental sustainability being promoted or even limited according to the way of life built.